William Shakespeare's Richard III - Rosenblatt, Arthur S. (Barron's book notes., 1985)
A guide to reading "Richard III" with a critical and appreciative mind encouraging analysis of plot, style, form, and structure. Also includes background on the author's life and times, sample tests, term paper suggestions, and a reading list.